Guru Dalam Mengembangkan Kreativitas Anak Usia Dini Di Paud Al Kifah It Mandailing Natal - Nasution, Lenni Maharani; Harahap, Abdi Syahrial (Peneliti.net, 2024)
This research aims to analyze and document the strategies used by teachers at Al Kifah IT Early Childhood Education (PAUD) in Mandailing Natal in developing the creativity of early childhood. Creativity is an important aspect in children's development which includes the ability to think creatively, imagine and find innovative solutions to problems. This research uses qualitative research methods by collecting data through participant observation, interviews with teachers, and documentation analysis. The results of this research reveal a number of strategies used by PAUD Al Kifah IT teachers in developing children's creativity: Learning Environment that Supports Creativity: Teachers create a learning environment that stimulates creativity by providing a variety of resources, such as creative toys, storybooks, and art supplies, that allow children to explore and express. Open-ended Questions and Problem Solving: Teachers often ask open-ended questions that encourage children to think creatively and seek solutions to given problems or challenges. This approach has important implications in the context of early childhood education, because creativity is the basis for children's problem-solving abilities, innovation, and intellectual and social development. Thus, this research provides valuable insight into educational practices that support the development of creativity in early childhood in early childhood settings. These findings can be a source of inspiration for other educators who want to improve creativity education in preschool children